Development of a heat exchanger device- regenerator for high-temperature gas heating - D. A. Bazykin; A. I. Sukhov; A. V. Barakov (Известия высших учебных заведений: Проблемы энергетики, 2019)
The urgency of the task is to develop a heat exchanger-regenerator designed for high- temperature heating of gaseous media, which are used in various technological schemes of the petrochemical, gas processing, energy and other industries. The developed heat exchanger has high performance due to the developed heat exchange surface, reliability due to the fact that the inner and outer pipes are movable relative to each other with linear dimensions compensation, it is simple to manufacture, does not require the use of an intermediate heat carrier, can be used as a heating coolant combustion products of untreated, low-grade gaseous fuel. At the same time, it is possible to equip the developed apparatus with a convection heat exchanger for more efficient use of the heat of the fuel combustion products. The article describes the proposed design, the principle of operation of this heat exchanger-regenerator. A review of the technical literature has been carried out, the main advantages of the device are shown in comparison with the currently known domestic and foreign counterparts. The paper presents the main calculated dependencies used in the design, as well as the results of the calculations. The possibility of using the proposed heat exchanger as part of a gas turbine unit used as an autonomous power source is considered, as well as information about technological processes in which it can be used. In conclusion, we can say that the developed heat exchanger has high performance, differs in the ability to work at high temperatures without violating the integrity of the structure, does not require the use of an intermediate heat carrier, and is to be used in many industries.